2016
DOI: 10.1186/s12936-016-1286-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing outdoor host-seeking in Anopheles gambiae over 6 years of vector control on Bioko Island

Abstract: BackgroundVector control through indoor residual spraying (IRS) has been employed on Bioko Island, Equatorial Guinea, under the Bioko Island Malaria Control Project (BIMCP) since 2004. This study analyses the change in mosquito abundance, species composition and outdoor host-seeking proportions from 2009 to 2014, after 11 years of vector control on Bioko Island.MethodsAll-night indoor and outdoor human landing catches were performed monthly in the Bioko Island villages of Mongola, Arena Blanca, Biabia and Balb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 29 publications
3
79
0
Order By: Relevance
“…gambiae s.l. from inside to outside biting [25,[27][28][29]. In addition, based on our experience in the eld, the human population spends much more time outside than inside because of the heat as the study area is located in a Sahelian eco-climatic zone of Mali.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae s.l. from inside to outside biting [25,[27][28][29]. In addition, based on our experience in the eld, the human population spends much more time outside than inside because of the heat as the study area is located in a Sahelian eco-climatic zone of Mali.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, through intraspecific behavioural shifts in biting time, location and host preference, malaria-transmitting mosquitoes avoid exposure to insecticides, feeding on humans when most people are not protected [129], jeopardising the current control strategy in Africa primarily based on indoor application of insecticides [130][131][132]. Recent studies conducted in West and East Africa have shown that indoor application of insecticides may induce intraspecific behavioural shifts towards early biting, exophagic biting and exophilic resting behaviour in malaria-transmitting mosquitoes [130,131,133]. Similarly, current studies conducted in Central Africa showed a comparable shift towards exophilic resting behaviour [134].…”
Section: Behavioural Resistance To Insecticides Used In Public Healthmentioning
confidence: 99%
“…In addition, the behavioral changes of vector and the shift in species composition resulting from the use of LLINs may also compromise the efficacy of malaria control tools. [18][19][20][21][22][23][24] Indeed, the strategy to use LLINs is mainly effective against those malaria vectors that are mostly anthropophilic, and bite and rest inside rooms. 25 These are the distinctive characteristics of the main African malaria vectors that belong to the Anopheles gambiae complex and the Anopheles funestus group.…”
Section: Introductionmentioning
confidence: 99%